2003
DOI: 10.1128/ec.2.5.1099-1114.2003
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Modifications Required for Cell Surface Localization and Function of the Fungal Adhesin Aga1p

Abstract: Adherence of fungal cells to host substrates and each other affects their access to nutrients, sexual conjugation, and survival in hosts. Adhesins are cell surface proteins that mediate these different cell adhesion interactions. In this study, we examine the in vivo functional requirements for specific posttranslational modifications to these proteins, including glycophosphatidylinositol (GPI) anchor addition and O-linked glycosylation. The processing of some fungal GPI anchors, creating links to cell wall ␤-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 81 publications
1
33
0
Order By: Relevance
“…Investigation of this question is complicated by the observation that GPI proteins are always found to some extent in both locations (16,87,88). Indeed, recent information shows that GPI-linked wall proteins are often cross-linked into the wall by other mechanisms as well, including glutamine-dependent transesterification (22,64) and disulfide bond formation (52). The result of these complications is that the proportion of proteins localized within the wall has usually been underestimated, a result of incomplete release of the wall-bound proteins as well as because of poor electrophoresis and blotting of yeast proteoglycans (88).…”
Section: Pre-gpi and Gpi Signal Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of this question is complicated by the observation that GPI proteins are always found to some extent in both locations (16,87,88). Indeed, recent information shows that GPI-linked wall proteins are often cross-linked into the wall by other mechanisms as well, including glutamine-dependent transesterification (22,64) and disulfide bond formation (52). The result of these complications is that the proportion of proteins localized within the wall has usually been underestimated, a result of incomplete release of the wall-bound proteins as well as because of poor electrophoresis and blotting of yeast proteoglycans (88).…”
Section: Pre-gpi and Gpi Signal Sequencesmentioning
confidence: 99%
“…This length would allow the ligand-binding regions of Epa1p, Als1p, and Aga2p to be displayed far enough from the wall surface to be active (78). In these cases, deletion of some amino acids from this region results in inactive adhesins (26,52,85,106). In an elegant study, Frieman and Cormack showed that when this region was deleted from Eap1p, the adhesion domain was present in the wall but was not sufficiently exposed to bind to its ligand because the stalk was too short (26).…”
Section: Ser/thr-rich Stalksmentioning
confidence: 99%
“…These studies show that blocking access to glycoproteins with sugar group binding compounds, such as concanavalin A, interferes with the adhesive capacity of fungal cells (Buck and Andrews, 1999). Thus, current evidence suggests that protein glycosylation plays a key role in the adhesive properties of fungal cells (Buurman et al, 1998;Huang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal adhesion interactions are mediated by cell surface proteins termed adhesins, which belong to a general class of cell wall proteins typically attached to the cell surface via GPI anchors (Orlean 1997;Kapteyn et al 1999;Sundstrom 2002;Huang et al 2003). In S. cerevisiae, the agglutinin genes AGA1, AGA2, SAG1/AGa1, and another mating-specific adhesin FIG2 are involved in the mating process (Lipke and Kurjan 1992;Sprague and Thorner 1992;Erdman et al 1998;Jue and Lipke 2002;Zhang et al 2002).…”
mentioning
confidence: 99%
“…The functions of these domains may be divided into two major categories: domains dedicated to adhesion interactions that are either protein-protein, lectin or transglutaminase mediated in nature, and domains whose repetition serves to increase the distance between the C-terminal GPI-associated plasma membrane and cell wall anchoring domain and the typically N-terminally distributed adhesion-mediating domains (Lipke 1996;Guo et al 2000;Frieman et al 2002;Huang et al 2003;Verstrepen et al 2004Verstrepen et al , 2005Kaur et al 2005;Dranginis et al 2007). Although most GPI-anchored adhesins contain both such types of domains, assigning individual domains to either of these categories may not be done exclusively in all cases, since recent work suggests that some repeated domains may influence not only overall size, but also aspects such as the hydrophobicity of adhesin proteins and therefore the cell surface when expressed in sufficient quantity (Verstrepen et al 2004;Fidalgo et al 2006;Ishigami et al 2006;Dranginis et al 2007).…”
mentioning
confidence: 99%